DESIGN, IMPLEMENTATION, AND EVALUATION OF POWER SUPPLY UNIT FOR PORTABLE METAL ORGANIC FRAMEWORK (MOF) FILTER REACTOR WITH SPECTROPHOTOMETER FOR INDIGO CARMINE DYE - Raihan Elfazri, Muhammad
This paper describes the power supply system for the Metal Organic Framework (MOF) filter reactor. The TA232401004 group intends to develop a module that integrates the stages of wastewater filter testing. In this paper, the authors describe the design and integration of a power supply system for a Metal Organic Framework (MOF) filter reactor that allows the reactor to be portable .The function of the system is to provide power to other subsystems through 12 V output when the power switch is turned on and (if needed) the power supply is connected to the grid. Two system designs are presented: a system using batteries and a Battery Management System (BMS) that allows use without connection to the grid, and one using a Switched-Mode Power Supply (SMPS) that ensures power output. Using 8 batteries as 2 packet of 4 batteries paralleled, the system with BMS could supply the load given for 3 iterations and 2 hours. When checking the output at each component during maximum load, it is shown that the voltage is unstable and only could reach around 9-10 V. By repeating the test with the load set according to the usage stage, it was found that undervoltage and instability occurred during the filtration process due to the PTC heaters drawing large power intermittently. Further inspection of the power supply components showed that the battery energy capacity (mAh) specification only reached 1500-2000 mAh out of the required 3500 mAh. To fulfill the power needs, additional cell packs or purchasing a battery with a higher capacity is required which is costly, making it impractical. Therefore, SMPS, which has a greater power output was chosen, while sacrificing flexibility of usage.